Wireless Mobile Communication and Healthcare Third International Conference, MobiHealth 2012, Paris, France, November 21-23, 2012, Revised Selected Papers - Godara, Balwant; Nikita, Konstantina S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Third International Conference on Wireless Mobile Communication and Healthcare, MobiHealth 2012, and of the two workshops: Workshop on Advances in Personalized Healthcare Services, Wearable Mobile Monitoring, and Social Media Pervasive Technologies (APHS 2012), and Workshop on Advances in Wireless Physical Layer Communications for Emerging Healthcare Applications (IWAWPLC 2012), all held in Paris, France, in November 2012. The 39 revised full papers presented were carefully reviewed and selected from 66 submissions. The papers are organized in topical sections covering wearable, outdoor and home-based applications; remote diagnosis and patient management; data processing; sensor devices and systems; biomedical monitoring in relation to society and the environment; body area networks; telemedicine systems for disease-specific applications; data collection and management; papers from the invited session "Implants"; papers from the IWAWPLC and APHS workshops.
A Complete TV-Based Solution for Remote Patient Monitoring and Care -- Biomedical Monitoring of Non-hospitalized Subjects Using Disruption-Tolerant Wireless Sensors -- ANT+ Medical Health Kit for Older Adults -- Smart Media Services through TV Sets for Elderly and Dependent Persons -- User Centered Design of an Interactive Mobile Assistance and Supervision System for Rehabilitation Purposes -- One IMU is Sufficient: A Study Evaluating Effects of Dual-Tasks on Gait in Elderly People -- On the Use of Nomadic Relaying for Emergency Telemedicine Services -- A Mobile Healthcare System for Sub-saharan Africa -- A Novel Method for Feature Extraction in Vocal Fold Pathology Diagnosis -- Monitoring Respiratory Sounds: Compressed Sensing Reconstruction via OMP on Android Smartphone -- A Personalized Model for Galvanic Coupling in Intrabody Communication Systems -- Switching from Traditional Medical Applications to Mobile Devices: Cardiac and Cochlear Implants -- Persuasive Design in Mobile Applications for Mental Well-Being: Multidisciplinary Expert Review -- Fundamental Study for Optical BAN -- Spectrum Sensing Improvement in Cognitive Radio Networks for Real-Time Patients Monitoring -- Theoretical Analysis and Modeling of Link Adaptation Schemes in Body Area Networks -- Mobile Multi-parametric Sensor System for Diagnosis of Epilepsy and Brain Related Disorders -- An Integrated Broker Platform for Open eHealth Domain -- Data Processing from mHealth Patient Data Acquisition Related to Extracting Structured Data from EH Records -- Performance Evaluation of EC-ElGamal Encryption Algorithm for Wireless Sensor Networks -- An Analog Front-End and ADC Integrated Circuit for Implantable Force and Orientation Measurements in Joint Prosthesis -- Active Textile Antennas as a Platform for More Energy-Efficient and Reliable Wireless Links in Healthcare -- Identifying Physiological Features from the Radio Propagation Signal of Low-Power Wireless Sensors -- Cooperative and Low-Power Wireless Sensor Network for Efficient Body-Centric Communications in Healthcare Applications -- A Distributed Dynamic Mobility Architecture with Integral Cross-Layered and Context-Aware Interface for Reliable Provision of High Bitrate mHealth Services -- Depression Diagnostic and Screening Tools Using Android OS Platform.
Keywords: Computer science; Medical records -- Data processing; Computer Communication Networks; Data mining; Computer Science; Health Informatics; Computers and Society; Computer Communication Networks; Data Mining and Knowledge Discovery